2001
DOI: 10.1021/jp0110713
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Time-Resolved Fluorescence Study of Photoisomerization of trans-Azobenzene

Abstract: The electronic relaxation and isomerization mechanism of trans-azobenzene after the S 2 (ππ*) r S 0 photoexcitation were investigated in solution by steady-state and femtosecond time-resolved fluorescence spectroscopy. In the steady-state fluorescence spectrum, two bands were observed with their peaks at ∼390 nm (∼25 750 cm -1 ) and ∼665 nm (∼15 000 cm -1 ). These fluorescence bands showed good mirror images of the S 2 (ππ*) r S 0 and S 1 (nπ*) r S 0 absorption bands, so that they were assigned to the fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
352
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(397 citation statements)
references
References 36 publications
40
352
5
Order By: Relevance
“…Multi-configuration calculations [19,23] indicate that an excited state composed of two electrons promoted from the HOMO to the LUMO has a barrier-less potential energy profile along the rotation path. That excited state is not accurately described within either TDLDA or BSE approaches in the current two-particle approximation.…”
Section: Applicationsmentioning
confidence: 99%
“…Multi-configuration calculations [19,23] indicate that an excited state composed of two electrons promoted from the HOMO to the LUMO has a barrier-less potential energy profile along the rotation path. That excited state is not accurately described within either TDLDA or BSE approaches in the current two-particle approximation.…”
Section: Applicationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] An earlier study on the absorption spectra indicated that the first and second excited states of both cis-and trans-azobenzene were attributed to nπ * and ππ * excitations, respectively. 1,4,11 Quantum yields of the isomerizations for cis-and trans-azobenzene were reported to be different between nπ * and ππ * excitations.…”
Section: Introductionmentioning
confidence: 99%
“…In solution optical excitation of the π−π * and n−π * transitions reversibly switches between these conformers. The (sub)picosecond time constant of the isomerization reaction in solution yields a quantum efficiency close to unity [1,2], and switching is possible even with a photodiode. In contrast, no successful reversible switching by optical excitation has been achieved to date when the bare azobenzene molecule is adsorbed at a metal surface.…”
Section: Introductionmentioning
confidence: 99%